2012
DOI: 10.1152/ajpendo.00597.2011
|View full text |Cite
|
Sign up to set email alerts
|

Increased intramyocellular lipids but unaltered in vivo mitochondrial oxidative phosphorylation in skeletal muscle of adipose triglyceride lipase-deficient mice

Abstract: Adipose triglyceride lipase (ATGL) is a lipolytic enzyme that is highly specific for triglyceride hydrolysis. The ATGL-knockout mouse (ATGL−/−) accumulates lipid droplets in various tissues, including skeletal muscle, and has poor maximal running velocity and endurance capacity. In this study, we tested whether abnormal lipid accumulation in skeletal muscle impairs mitochondrial oxidative phosphorylation, and hence, explains the poor muscle performance of ATGL−/− mice. In vivo 1H magnetic resonance spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Unexpectedly, changes in ATGL-mediated TAG hydrolysis in skeletal muscle in vivo do not significantly impact these parameters. These results are consistent with reports demonstrating IMTG accumulation but unaltered in vivo mitochondrial function in skeletal muscle of GAKO (42) and muscle-specific CGI-58 knockout mice (43). Thus, in striking contrast to cardiac muscle (21), in vivo modulation of TAG hydrolysis in skeletal muscle does not influence PPAR target genes or mitochondrial phenotypes.…”
Section: Discussionsupporting
confidence: 93%
“…Unexpectedly, changes in ATGL-mediated TAG hydrolysis in skeletal muscle in vivo do not significantly impact these parameters. These results are consistent with reports demonstrating IMTG accumulation but unaltered in vivo mitochondrial function in skeletal muscle of GAKO (42) and muscle-specific CGI-58 knockout mice (43). Thus, in striking contrast to cardiac muscle (21), in vivo modulation of TAG hydrolysis in skeletal muscle does not influence PPAR target genes or mitochondrial phenotypes.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, our findings are similar to those recently reported in adipose triglyceride lipase knockout (ATGL-KO) mice in which the force production was lower as compared to controls while a similar PCr depletion was observed for the two groups. The authors also concluded that ATGL-KO mice had a higher energy cost per contraction (or a lower contractile efficiency) as compared to controls [41].…”
Section: Discussionmentioning
confidence: 98%
“…Over the last decade, analysis of PCr recovery kinetics has been extensively used in order to investigate in vivo skeletal muscle mitochondrial oxidative capacity [41], [42]. Previous animal studies reported PCr recovery times typically ranging from ∼50 sec to ∼160 sec according to the end-of-exercise pH values [31], [41], [43]. From a methodological point of view, it should be pointed out that PCr recovery is usually fitted with a monoexponential function so that the temporal resolution of the raw dataset is of utmost importance for an accurate measurement of the corresponding variables.…”
Section: Discussionmentioning
confidence: 99%
“…Intramyocellular lipid (IMCL) levels were assessed by single‐voxel 1 H MRS at 7 T from the tibialis anterior muscle as described previously (18).…”
Section: Methodsmentioning
confidence: 99%